Heightened expression of type I interferon signaling genes in CD4+ T cells from acutely HIV-1–infected women is associated with lower viral loads - El-Badry, Elina; Chen, Luxiao; Ghneim, Khader; Li, Ziyi; Brooks, Kelsie; Rhodes, Jake; Sekaly, Rafick; Kilembe, William; Allen, Susan; Wu, Hao; Hunter, Eric (Frontiers in Immunology, 2025)
Sex differences play a role in the pathogenesis of a number of viral diseases. In HIV-1, several studies have reported that chronically infected women have significantly lower plasma viremia than men, although the exact mechanism by which this occurs has yet to be identified. We have performed bulk RNA-seq experiments comparing gene expression between CD4+ T cells from acutely HIV-1–infected men and women in Zambia, because we observe lower viral load (VL) despite higher CD4+ T-cell activation in these women during acute/early infection. In a univariate analysis, we have identified a number of differentially expressed genes in naïve, central memory, and effector memory CD4 T cells of women with consistent elevated expression of genes linked to type 1 interferon (IFN) signaling. Moreover, after controlling for differences in VL and CD4+ T-cell count, genes within the type I IFN signaling pathway were further shown to be more highly expressed in women, whereas those genes more highly expressed in men showed no such enrichment. A subset of the genes highly expressed in women was further identified, including several involved in type I IFN signaling in response to viral infections (IRF7, DDX58, SAMHD1, OAS2, and TRIM14), that both are more highly expressed in CD4+ T cells from women and negatively correlated with VL, suggesting that they play a role in the comparative control of VL observed in women.